Maternal selenium, copper and zinc concentrations in pregnancy associated with small-for-gestational-age infants - Mistry, Hiten D.; Kurlak, L.O.; Young, Scott D.; Briley, Annette; Broughton Pipkin, Fiona; Baker, Philip; Poston, Lucilla (Wiley, 2014)
Pregnancy during adolescence increases the risk of adverse pregnancy outcome, especially risk of small-for gestational-age (SGA) birth, which has been linked to micronutrient deficiencies. Likewise, smoking has been shown to be related with lower micronutrient concentrations. Different ethnicities have not previously been examined. We used a subset from a prospective observational study, the About Teenage Eating (ATE) study consisting of 126 pregnant adolescents (14-18 years old) between 28-32 weeks' gestation. Micronutrient status was assessed by inductively-coupled mass spectrometry. Smoking was assessed by self-report and plasma cotinine, and SGA was defined as infants born < 10th corrected birthweight centile. The main outcome measures were: 1) Maternal plasma selenium, copper and zinc concentrations in adolescent mothers giving birth to SGA versus appropriate-for-gestational-age (AGA) infants. 2) Comparison of micronutrient concentrations between women of different ethnicities and smoking habits. The plasma selenium (mean ± SD [95% CI]) concentration was lower in the SGA (n = 19: 49.4 ± 7.3 [CI: 45.9, 52.9] μg/L) compared to the AGA (n = 107: 65.1 ± 12.5 [CI: 62.7, 67.5] μg/L; P < 0.0001) group. Smoking mothers had a lower selenium concentration compared to non-smokers (P = 0.01) and Afro-Caribbean women had higher selenium concentrations compared to White Europeans (P = 0.02). Neither copper nor zinc concentrations varied between groups, but selenium and copper were moderately correlated (P < 0.05). Selenium is an essential trace element which exerts its biological effects through the expression of a variety of important selenoproteins. Low plasma selenium concentration in adolescent mothers could contribute to the risk of delivering an SGA infant, possibly through lowering the placental antioxidant defence, thus direclty affecting fetal growth. The differences in plasma selenium between different ethnicities may relate to variation in nutritional intake, which requires further investigation.